Environmental protection and fuel consumption reduction by flameless combustion technology: a review - Hosseini, S. E. (2013)
In recent years global fuel consumption has increas edin the world due to modernization and progress in the standard of living. The conspic uous rate of carbon dioxide and nitrogen oxide released to the environment and fuel resources are depleted day by day due toinconsiderate fuel consumption. Requirement for efficient use of any k inds of fuel has become the other concern due to the oil crisis and limitation of fuel resources. In combustion process, the abatement of pollutants often associates with efficiency loss. In the other word, high efficiency and low pollutant which are the main requirements of combustion are not fulfill ed by the existing combustion. Today, flameless combustion has received more attention because of i ts low NOx emission and significant energy saving. Generally, compatibility between high perfo rmance and low NOx emission has been observed by preheated air application and changing the combustion characteristics from traditional flame to flameless mode. This paper aims to review the concepts and the applications of flameless combustion and gathers useful information to unders tand the necessity of transient from traditional flame mode to flameless combustion.